Policy Versus Practice: Facilitators and Barriers of Chronic Care Integration in Dutch General Practice – a Survey Study - Toine E. P. Remers; Simone A. van Dulmen; Erik W. M. A. Bischoff; Florien M. Kruse; Marcel G. M. Olde Rikkert; Patrick P. T. Jeurissen (International Journal of Integrated Care)
Introduction: Multimorbidity challenges quality and sustainability of healthcare systems. Care groups were introduced in the Netherlands to promote integration of chronic primary care, but it remains unknown to which degree they facilitate this. This study therefore aims to determine whether Dutch general practices perceive themselves to be capable of delivering integrated chronic care and uncover the role of care groups. Methods: We performed a survey study amongst 39 care groups and 65 healthcare providers within general practices (GPs and nurse practitioners). Results: 43% of healthcare providers within general practices are (very) dissatisfied with capabilities for chronic care to patients and 56% do not feel capable of delivering integrated care. Care groups and providers show alignment in their perception of some of the most important facilitators and barriers such as motivation and lack of time, but other factors are valued differently at both levels. Discussion: Our findings show inability of general practices to deliver integrated chronic care despite a health system that is inherently supportive of care integration and point to a mismatch between barriers and facilitators amongst practices and care groups, resulting in providers partly relying on their motivation in accommodating integrated chronic care. Conclusion: General practices are not sufficiently supported by care groups and national policies in delivering integrated chronic care. The identified mismatch between policy and practice warrants redesign of support from care groups to align policies with identified barriers and facilitators at the provider level.